2014
DOI: 10.1007/s10393-014-0962-7
|View full text |Cite
|
Sign up to set email alerts
|

Representative Seroprevalences of Human and Livestock Brucellosis in Two Mongolian Provinces

Abstract: Mongolia implemented a brucellosis livestock mass vaccination campaign from 2000 to 2009. However, the number of human cases did not decline since 2004 and the current epidemiological situation in Mongolia was uncertain. The objective of this study was to estimate the representative seroprevalences of humans and livestock in two provinces in view of their comparison with officially reported data. A representative cross-sectional study using cluster sampling proportional to size in humans, sheep, goats, cattle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
1
30
1
2
Order By: Relevance
“…Between June and September 2010, surveys were conducted in Sukhbaatar and Zavkhan provinces, selected for convenience. 7 Between November 2011 and January 2012, the same surveys were conducted in a further six provinces: Arkhangai, Khuvsgul, Selenge, Uvs, Umnugovi and Govi-Altai (Figure 1). In each province, four districts were selected using simple randomization in Excel (the rand () command).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Between June and September 2010, surveys were conducted in Sukhbaatar and Zavkhan provinces, selected for convenience. 7 Between November 2011 and January 2012, the same surveys were conducted in a further six provinces: Arkhangai, Khuvsgul, Selenge, Uvs, Umnugovi and Govi-Altai (Figure 1). In each province, four districts were selected using simple randomization in Excel (the rand () command).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Livestock rearing is still based on a traditional nomadic system, and various animal species comingle while being raised, so brucellosis can be easily transmitted (13). Therefore, it is important to identify the characteristics of Mongolian Brucella strains accurately using phenotypic and molecular typing.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies examining brucellosis in Mongolia have mainly focused on serological monitoring and prevalence in humans and domestic animals (1,12,13). Previous analysis of seminomadic herders in central Mongolia also demonstrated that human brucellosis was related to animal brucellosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on seroprevalence of brucellosis in high risk human populations in countries which are endemic for the disease have shown that the seroprevalence figures are as follows: 8.8% in Kyrgyzstan; 2.2-21.6% in Bangladesh; 6.9% in Pakistan; 24.1% in Nigeria; 27.3% in Mongolia and 15% in Saudi Arabia [34][35][36][37][38][39].…”
Section: Seroprevalence and Blood Transfusion-related Brucellosismentioning
confidence: 99%